Using digital forensics in policing, 2018-2022 - Wilson-Kovacs, Dana (UK Data Service, 2023)
This project has examined the application of digital forensics (DF) in police investigations and the operational, organisational and professional opportunities and challenges this presents. The objectives of the project have been: 1. To appraise current DF provision and processes in four DFUs that are part of a forensic collaboration – both individually and as part of a regional framework – to understand the organisation and use of DF in investigations and identify best practices locally and regionally 2. To observe how DF processes and practices in the four units observed compare with those of other DFUs nationally 3. To understand how DF contributes to the analysis and interpretation of digital trace and how police forces, the Crown Prosecution Service (CPS) and defence teams use digital evidence 3. To assess how occupational cultures, organisational arrangements and regulatory requirements impact on inter and intra-professional exchanges and understandings of professionalism and expertise 4. To examine how DF fits in the wider delivery of forensic service support for the four forces, together with other in-house services such as crime scene investigation, and explore this process nationally 5. To document the concerns and expectations of key stakeholders, inform policy developments and support the development of local, regional and national approaches to the application of DF in policing Some of the areas the project has focused on consist of the management of digital trace within and outside DF units (DFUs), the impact of ISO17025 accreditation, the rise in demand for mobile phone analysis, risk assessment procedures, welfare and wellbeing of staff, professional development and support, and training. The implications of the findings are currently explored through ongoing analysis. Common themes raised by the DF practitioners interviewed included (1) change fatigue following the start of the collaboration and subsequent processes of accreditation, (2) sparse resources, (3) officers’ partial understanding of how DF can contribute to investigations and their mixed ability to present a digital investigative strategy when submitting exhibits for DF analysis, (4) wellbeing, burnout and stress, (5) the lack of recognition for the service provided, (6) professional development and career progression opportunities and (7) cultural and organisational tensions as part of working in collaboration. Equally, the officers interviewed outlined a number of related issues pertaining to: a) delays in the processing of digital trace, b) the impact of accreditation on DF service delivery, c) disclosure processes, d) CPS pressures and queries for additional evidence at very short notice, e) the lack of assistance for DMIs and CAs, f) senior investigating officers’ and police management’s uneven understanding of DF and the investment it required, g) frontline officers lack of digital awareness, especially when identifying, preserving and using digital trace and h) expectations working within the police service. Digital evidence can reveal a suspect's intent to commit an offence and help establish when events occurred, where victims and suspects were and with whom they communicated. It has been increasingly used in examinations of homicides, sex crimes, missing persons, child sexual abuse, drug dealing, fraud and theft of personal information, as well as in civil disputes. As the volume of cases requiring digital forensic analysis and the amount of information to be processed in each case have risen rapidly in recent years, law enforcement agencies are struggling to address this demand. In this context, social science research is needed to illuminate how current practices can be improved and the ways in which the usefulness of digital evidence in crime detection can be maximized while preserving ethical acceptability, civil liberties and protecting both the victims and the wrongly accused. To date however, these critical issues remain under-explored and little is known about the deployment of digital forensic evidence in police inquiries and the organiational, professional and societal issues it raises. This project aims to offer a theoretically grounded and empirically based ethnographic analysis of the digital forensic resources, practices and expertise mobilised to provide intelligence for on-going investigations and aid the prosecution of suspects. Focusing on areas of improvement prioritised with the input of digital forensics (DF) practitioners working across four police forces as part of a regional forensic collaboration, its main objectives are to examine current provision in the constabularies covered by this organizational arrangement and explore how DF capabilities are used in the production of digital evidence. The project will employ qualitative methodologies to analyse the interactions and exchanges between different occupational groups and render visible this rarely explored socially and politically sensitive domain. A focus on the transformation of digital data into evidence and its trajectory to the final stage before prosecution, will enable the observation of DF knowledge and routines (1) as they unfold and (2) at different points in the investigative process. It will bring into relief operational procedures and dependencies, professional tensions, regulatory dynamics and distinct understandings of DF capabilities. The potential benefits of this project are multi-layered: Conceptually, the project will contribute to sociological and criminological studies on the seldom explored application of forensic technologies in policing. The analysis will also inform and update wider socio-legal, crime and police studies approaches to assessing the contribution of forensic science to criminal justice outcomes, and social science literature on how various stakeholders understand the role of DF in police investigations. Methodologically, the project will facilitate practitioners' engagement with and through its design, and provide novel insights on the role of social science research in documenting, establishing and sustaining dialogue between different communities of practice. At a practical level, the project will provide an in-depth understanding of current DF arrangements. The study will augment initiatives by police forces to improve performance by educating stakeholders about the ways in which DF can contribute to criminal investigations. It will do so in an organizationally reflexive way, with a view to foster cross-sector co-operation and exchange and improvements. The findings will help identify the gaps in DF resources and tensions in its delivery and impact directly on current practices. They will promote dialogue between providers and users, and inform the future training of investigative staff. At a policy level, the findings will contribute to better informed decision making. With a focus on 'What Works' in DF they will help promote best practices and lead to a more efficient delivery of DF provision.